2009
DOI: 10.1371/journal.pntd.0000497
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Onchocerciasis Elimination with Ivermectin Treatment in Endemic Foci in Africa: First Evidence from Studies in Mali and Senegal

Abstract: BackgroundMass treatment with ivermectin is a proven strategy for controlling onchocerciasis as a public health problem, but it is not known if it can also interrupt transmission and eliminate the parasite in endemic foci in Africa where vectors are highly efficient. A longitudinal study was undertaken in three hyperendemic foci in Mali and Senegal with 15 to 17 years of annual or six-monthly ivermectin treatment in order to assess residual levels of infection and transmission and test whether ivermectin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
334
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(348 citation statements)
references
References 33 publications
9
334
0
2
Order By: Relevance
“…22 The guidelines developed were based on a detailed review of the 2001 World Health Organization (WHO) criteria for certification of elimination of onchocerciasis, tropical disease research (TDR) studies, and guidelines used by the Onchocerciasis Elimination Program for the Americas. [23][24][25] The Uganda criteria include three indicators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The guidelines developed were based on a detailed review of the 2001 World Health Organization (WHO) criteria for certification of elimination of onchocerciasis, tropical disease research (TDR) studies, and guidelines used by the Onchocerciasis Elimination Program for the Americas. [23][24][25] The Uganda criteria include three indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Microfilaria (mf) prevalence in skin snips must be less than 5% in all sampled communities and less than 1% in 90% of sampled communities. 24 Serological assessments. Infection rates in children must be 0.1%.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9] An important study in hyperendemic foci in Mali and Senegal showed that 15-17 years of annual ivermectin treatment had eliminated onchocerciasis transmission in the north and center of the Rio Faleme focus and that mass treatment could be safely stopped. 10 The two criteria used by Diawara and others 10 to make this determination were entomological (< 0.5 infected flies/1,000 flies) and epidemiological (< 5% mf prevalence in all communities examined and < 1% in 90% examined). It is important to note that, in the south of the Rio Falema focus, there were seven villages with mf prevalence between 1% and 13% after 15-17 years of annual treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only drug available for mass treatment is ivermectin (Mectizan®, Merck), which was originally marketed as a veterinary anthelmintic (7). Although this drug has proven successful in reducing morbidity, the risk of severe skin or ocular disease and decrease of microfilarial loads (>99%) after 14 d of treatment, it only has modest effect on adult worms and must be continuously administered over decades (8,9); and it now appears that ivermectin-resistance is emerging (10). Thus, there is a crucial need to identify new drug targets and agents that can effectively treat onchocerciasis.…”
mentioning
confidence: 99%